1980
DOI: 10.1007/bf01065598
|View full text |Cite
|
Sign up to set email alerts
|

Variation in courtship sounds among three geographical strains ofDrosophila mercatorum

Abstract: Sound recordings of courtship in Drosophila mercatorum were analyzed with an oscilloscope. Sounds in this species consist of two kinds of pulses, referred to as the A and B sounds, respectively. These differ from each other in their oscilloscope pattern and in the behavior accompanying them. A comparative study of three strains from widely separated geographical regions (New York, El Salvador, and Hawaii) revealed significant differences among strains in the interpulse interval (ipi) of the A sound. The ipi of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Although large X chromosome effects have been described in one study of sexual isolation in males (6), they were not found in two other experiments (5,7). In some Drosophila species, characteristics of male courtship "song" may be predominantly located on the X chromosome, while in other species or characters the autosomes are more important (6,(26)(27)(28)(29). The connection between male mating song and sexual isolation is at any rate unclear: in the study of Kawanishi and Watanabe (6), sexual isolation mapped predominantly to the X chromosome but interspecific differences in mating song were predominantly autosomal.…”
Section: Resultsmentioning
confidence: 99%
“…Although large X chromosome effects have been described in one study of sexual isolation in males (6), they were not found in two other experiments (5,7). In some Drosophila species, characteristics of male courtship "song" may be predominantly located on the X chromosome, while in other species or characters the autosomes are more important (6,(26)(27)(28)(29). The connection between male mating song and sexual isolation is at any rate unclear: in the study of Kawanishi and Watanabe (6), sexual isolation mapped predominantly to the X chromosome but interspecific differences in mating song were predominantly autosomal.…”
Section: Resultsmentioning
confidence: 99%
“…1), and finally attempts to mount. The results obtained so far suggest that the A sound may be essential for the mate recognition and the B sound is more closely associated with copulation itself (Ikeda et al, 1980). In the present study, selection was carried out only with respect to the interpulse interval of the A sound (A11).…”
Section: Materials and Methods I Flies Usedmentioning
confidence: 99%
“…In fact a most remarkable difference is found in the pulse repetition rate between closely related species, subspecies or geographical strains (Bennet-Clark 1978Chang and Miller 1978;Cowling and Burnet 1981;Ewing and Bennet-Clark 1968;Ewing 1979;Ikeda et al 1980 ;Miller et al 1975 ;Waldron 1964). These findings suggest that inter-and intraspecific differentiation in the nature of courtship sounds first occurs in the 1) This paper is dedicated to Emeritus Professor Daigoro Moriwaki on the occasion of his 77th birthday.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…4 of Ewing and Bennet-Clark, 1968). Some Drosophila species sing several different songs (Ewing, 1969;von Schilcher, 1976;Chang and Miller, 1978;Ikeda et al, 1980;Crossley, 1986). Species of the D. bipectinata complex which belong to the ananassae subgroup are known as such species (Crossley, 1986).…”
Section: Discussionmentioning
confidence: 99%